Electromagnetic transients and gravitational waves from white dwarf disruptions by stellar black holes in triple systems. Issue 1 (13th May 2020) - Fragione, Giacomo; Metzger, Brian D; Perna, Rosalba; Leigh, Nathan W C; Kocsis, Bence
ABSTRACT: Mergers of binaries comprising compact objects can give rise to explosive transient events, heralding the birth of exotic objects that cannot be formed through single-star evolution. Using a large number of direct N -body simulations, we explore the possibility that a white dwarf (WD) is dynamically driven to tidal disruption by a stellar-mass black hole (BH) as a consequence of the joint effects of gravitational wave (GW) emission and Lidov–Kozai oscillations imposed by the tidal field of an outer tertiary companion orbiting the inner BH–WD binary. We explore the sensitivity of our results to the distributions of natal kick velocities imparted to the BH and WD upon formation, adiabatic mass loss, semimajor axes and eccentricities of the triples, and stellar-mass ratios. We find rates of WD–tidal disruption events (TDEs) in the range 1.2 × 10 −3 − 1.4 Gpc −3 yr −1 for z ≤ 0.1, rarer than stellar TDEs in triples by a factor of ∼3–30. The uncertainty in the TDE rates may be greatly reduced in the future using GW observations of Galactic binaries and triples with LISA . WD–TDEs may give rise to high-energy X-ray or gamma-ray transients of duration similar to long gamma-ray bursts but lacking the signatures of a core-collapse supernova, while being accompanied by a supernova-like optical transient that lasts for only days. WD–BH and WD–NS binaries will also emit GWs in the LISA band before the TDE. The discovery and identification of triple-induced WD–TDE events by future time domain surveys and/or GWs could enable the study of the demographics of BHs in nearby galaxies.